Alternative Teaching Methods in Electricity and Magnetism: A Literature Review - Rendon , Justine Dave L.; Doloretos, Nona Lyn; Capilitan, Lenilyn B.; Dumaan, Darlene L.; Mamada, Mary Joy D.; Mercado, Justine C. (Future Science / FSH-PH Publications, 2022)
Electricity and magnetism are known as an important topics in the physics and scientific curriculum at all levels, including elementary, secondary, and tertiary. Children can learn more about electricity and magnetism via discussion and activities. Electricity and magnetism also have applications in many aspects of our daily life as one of the fundamental areas and key concerns in physics. Traditional teaching methods are considered ineffective. Pupils who were taught using traditional methods or approaches, according to Jelicic et al. (2017), have a poor comprehension of basic electromagnetic principles and are often resistant to teachers' instruction and our education now is dependent on technology. In this review, the different alternative teaching methods used and preferred by other schools are being examined and its effect in teaching Electricity and Magnetism. The included studies in this literature review proved that the preferred teaching method to motivate and appreciate the importance of learning Electricity and Magnetism. Hence, students learn more through understanding concepts and the performance of things through active participation.